Strategic Dilemmas of Universities - Radosław Ryńca; Joanna Radomska (Contemporary Economics)
The article describes the difficult choices that are now concerning the universities. Authors are trying to show the dangers connected with insufficient strategic orientation and find the possible direction of adapting to the market conditions.